A noncommutative geometric LR rule - Edward Richmond; Vasu Tewari; Stephanie Van Willigenburg (Discrete Mathematics & Theoretical Computer Science, 2020)
The geometric Littlewood-Richardson (LR) rule is a combinatorial algorithm for computing LR coefficients derived from degenerating the Richardson variety into a union of Schubert varieties in the Grassmannian. Such rules were first given by Vakil and later generalized by Coskun. In this paper we give a noncommutative version of the geometric LR rule. As a consequence, we establish a geometric explanation for the positivity of noncommutative LR coefficients in certain cases.